O que Belo Monte não conteve: análise dos discursos insurgentes nas redes - Monteiro, Luísa Souto Maior (2018)
This research aims to study the outcomes of two widely known projects, Movimento Gota D’Água and Refugiados de Belo Monte, on Facebook. Through videos, crowdfunding websites and the creation of fan pages, the two movements were of paramount importance to value the anti-dam debate. Both advocated for the population and the peoples affected, who were “invisible”, gathering over one million signatures to interrupt the construction of the Belo Monte dam and raising more than 140 thousand reais for the psychological care of those who had to be relocated because of the dam. Having those two campaigns and how they unfolded on Facebook as a research corpus, this study bases itself on the discursive-semiotic analysis and socio semiotics (Landowski) to interpret the context of the construction of the Belo Monte hydroelectric power plant, the content of the videos used and the question of alterity. Also, the view of Patrick Charaudeau on the communication contract and the discourses used in the campaigns and Chantal Mouffe’s approach on the political are used to understand the performance of these campaigns. Ultimately this study intents to discuss how the construction of sense in the discourse of an insurgent communication happens